2020
DOI: 10.3390/genes11070716
|View full text |Cite
|
Sign up to set email alerts
|

Four Individuals with a Homozygous Mutation in Exon 1f of the PLEC Gene and Associated Myasthenic Features

Abstract: We identified the known c.1_9del mutation in the PLEC gene in four unrelated females from consanguineous families of Turkish origin. All individuals presented with slowly progressive limb-girdle weakness without any dermatological findings, and dystrophic changes observed in their muscle biopsies. Additionally, the neurological examination revealed ptosis, facial weakness, fatigability, and muscle cramps in all four cases. In two patients, repetitive nerve stimulation showed a borderline decrement and a high j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…A later report described the phenotype of four new homozygous carriers of the same c.1_9del deletion, belonging to four unrelated families, all of them consanguineous and originating from the same region as the previous cases, suggesting a common origin of the mutation. These patients presented with slowly progressive proximal muscular weakness, fatigue, and muscle cramps similar to the patients reported by Gundesli et al [ 105 ]; however, additionally, they showed clear myasthenic symptoms such as ptosis, nasal speech, tongue weakness, neck flexor and paraspinal muscle weakness, and mild scoliosis, with electromyographies showing myopathic changes; but, their skin was spared [ 106 ]. The second mutation identified in exon 1f, c.58G > T, p.Glu20X (reference sequence NM_201378.3), caused LGMDR17.…”
Section: Isoform-specific Plectin Kossupporting
confidence: 63%
“…A later report described the phenotype of four new homozygous carriers of the same c.1_9del deletion, belonging to four unrelated families, all of them consanguineous and originating from the same region as the previous cases, suggesting a common origin of the mutation. These patients presented with slowly progressive proximal muscular weakness, fatigue, and muscle cramps similar to the patients reported by Gundesli et al [ 105 ]; however, additionally, they showed clear myasthenic symptoms such as ptosis, nasal speech, tongue weakness, neck flexor and paraspinal muscle weakness, and mild scoliosis, with electromyographies showing myopathic changes; but, their skin was spared [ 106 ]. The second mutation identified in exon 1f, c.58G > T, p.Glu20X (reference sequence NM_201378.3), caused LGMDR17.…”
Section: Isoform-specific Plectin Kossupporting
confidence: 63%
“…Recently, the first mutations in alternative first exons have been described. A homozygous 9 bp deletion (c.1_9del1f) containing the initiation codon of exon 1f (and therefore resulting in the loss of isoform P1f) was identified in several patients suffering from limb-girdle muscular dystrophy (LGMDR17, previously denoted as LGMD2Q [ 13 ], MIM #613723); however, these patients did not show any overt signs of an epidermolytic skin disease [ 14 , 15 ]. Since then, another exon 1f-specific mutation (c.58G > T, p.E20X) has been reported, where three siblings suffered from MD and respiratory problems but who did not present with any skin involvement [ 16 ].…”
Section: Human Plectinopathiesmentioning
confidence: 99%
“…Up until now, 13 cases with LGMDR17 due to mutations in exon 1f have been published [ 14 , 15 , 16 ]. In general, most LGMDR17 patients suffered from early onset limb-girdle syndrome followed by several years of plateau.…”
Section: Clinical Phenotypes and Muscle-related Disease Manifestations Of Human Plectinopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mroczek et al review the particular molecular structure of PLEC, as well as its tissue-specific functions and associated phenotypes. The authors also investigate the role of plectin deficiency in congenital myasthenic syndromes by describing four patients carrying the PLEC c.1_9 mutation in homozygosity and suggesting a common origin of the mutation [ 8 ]. García-Solaesa et al describe, for the first time in a Spanish population, a new splice variant associated with a myopathic form of PGK1 deficiency.…”
mentioning
confidence: 99%